Behind the Wheel: Confidence and Naturalistic Measures of Driving Exposure Among Older Drivers. Issue 1 (January 2015) - Coxon, Kristy; Chevalier, Anna; Lo, Serigne; Ivers, Rebecca; Brown, Julie; Keay, Lisa
Driving confidence is thought to influence driving exposure among older drivers and may affect driver safety. Studies to date have relied primarily on self-reported measures of driving exposure to explore this relationship. The objective of this study was to explore the relationship between confidence and actual driving exposure among drivers aged 75 years and older. A cross-sectional analysis of survey data (function, confidence, personal circumstances) and naturalistic measures of driving exposure was conducted with 380 older drivers in northwest Sydney, Australia. Driving exposure, including total distance traveled, radius of travel from home, average trip distance, and nighttime driving, was measured for 1 week. The mean age of participants was 80 years. More males (n = 230) than females (n = 150) were enrolled. Successful instrumentation was achieved for 362 of 380 vehicles. Driving confidence was found to be independently associated with the farthest distance traveled from home, average trip distance, and night driving. Older drivers with lower confidence took shorter trips, stayed closer to home, and were less likely to drive at night. This study provided evidence of a responsive process in which drivers with lower confidence and poorer function were found to have different patterns of driving—specifically, driving in familiar areas, during daylight hours, and closer to home. It is likely that drivers in later life change their driving patterns to preserve safety and mobility. This understanding will help policy makers and educators shape responsive programs that help older drivers drive safely for as long as possible.